Population parameters and damage of Polyphagotarsonemus latus (Acari: Tarsonemidae) in Valencia orange (Citrus sinensis [L.] Osbeck) crop (2017)
Polyphagotarsonemus latus is one a major pest of Valencia orange in Colombia. To study its biology, it was established an experiment on young leaves of the Valencia orange at 25 ± 5°C, 70 ± 5% RH, and 12:12 L:D photoperiod. To characterize the nature of damage caused by this mite on leaves and young fruits, a trial in screenhouse conditions using young leaf and small fruits (0.1 - 0.3 cm in diameter) and fruits between 1.0–3.0 cm in diameter, which were infested with 5, 15 and 30 adult females of P. latus, was established. The total duration of life cycle was 3.2 days; the female had an oviposition period of 7.4 days and longevity 9.6 days. Life table parameters were as follows: net reproductive rate (Ro) = 93.3, intrinsic rate of natural increase (rm) = 1.2, finite multiplication rate (λ) = 3.7, doubling time (TD) = 0.6 days and generation time (T) = 3.4. The first signs of damage and shoot drop in newly developed shoots occurred between 7.0 and 11.8 days after infestation. Small fruit infested with 5-30 mites showed damage 2.4 days after infestation. Shoot drop started 7.0 days after infestation. In the case of fruits between 1.0 and 3.0 cm in diameter, the damage and the collapse of the structure was between 3.0 and 13.5 days, respectively. These results explain how a mite with a very short life cycle and huge biotic potential causes such severe damage in shoots and newly formed fruits of Valencia orange.